(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The Niger Delta basin is an important geological region of economic significance, serving as a critical oil and gas exploration area. Hence, there is a need to comprehend the geological history and environmental changes within the basin. Detailed palynofacies analyses, which provide crucial insights into paleoenvironmental conditions and organic matter preservation, are limited in the onshore depobelt. This study addresses this gap by focusing on a detailed palynofacies analysis of the PSA-1 well. Palynofacies analysis was carried out on ninety ditch-cutting samples from the PSA-1 well, located in the onshore Niger Delta Basin, to delineate the paleoenvironment of deposition across depths from 3520–6160ft. Standard acid maceration and microscopic examination were utilized; 200 palynomaceral counts were made per slide to determine the abundance and size fractions of each group. Four lithofacies units were identified through physical examination and textural characteristics, namely: shaly sandstone, clayey sandstone, mudrock, and shale facies. The palynofacies assemblage is quantitatively dominated by medium and small-sized fractions of Palynomaceral-1 (PM1) and Palynomaceral-2 (PM2), moderate amount of Palynomaceral-4 (PM4) with lesser amounts of Palynomaceral-3 (PM3). Moderate records of Structureless Organic Matter (SOM) was also observed. The consistent high percentage of phytoclasts PM1, PM2 and low to moderate percentage of amorphous organic matter (AOM) established a predominantly proximal depositional setting, suggesting a Terrestrial-Brackish swamp environment characterized by fluctuating energy conditions, such as a shifting deltaic or estuarine system.This study contributes to the depositional framework and organic matter distribution within the onshore Niger Delta and beyond.